Development of Test Cycle for Centrifugal Clutch of CVT Driven Scooters Intended for Urban Traffic Conditions - Dhruv U. Panchal; Bhavesh K. Patel (Automotive Experiences, 2022)
The present study deals with the development of a test cycle for the centrifugal clutch of continuously variable transmission (CVT) driven scooters. Centrifugal clutch experiences different duty cycles during the usage of scooters in city traffic and highways during its lifetime. Since the friction characteristics of the centrifugal clutch are controlled by acquired factors, it is difficult to predict ideal friction characteristics under all conditions. The wear of friction lining increases due to heat generated in the clutch assembly because of the repeated “stick-slip” phenomena. Therefore, an attempt has been made for developing à new test cycle by keeping the engagement frequency as a reference. Road load data for three different riding conditions have been collected and analyzed. The developed test cycle has been automated on the centrifugal clutch test bench and a new set of clutch liners was tested thoroughly. The surface roughness, thickness, and wear of clutch liners have been observed and evaluated against the field vehicles. For the surface roughness, maximum deviations of 3.74%, 3.36%, and 2.16% have been observed for trailing, middle and leading sections of clutch liners respectively. For the thickness, maximum deviations of 3.06%, 2.59%, and 3.14% have been observed for trailing, middle and leading sections of clutch liners respectively. The developed test cycle demonstrates a good correlation with field use.